2017
DOI: 10.1289/ehp194
|View full text |Cite
|
Sign up to set email alerts
|

Mortality due to Vegetation Fire–Originated PM 2.5 Exposure in Europe—Assessment for the Years 2005 and 2008

Abstract: Background:Vegetation fires can release substantial quantities of fine particles (PM2.5), which are harmful to health. The fire smoke may be transported over long distances and can cause adverse health effects over wide areas.Objective:We aimed to assess annual mortality attributable to short-term exposures to vegetation fire–originated PM2.5 in different regions of Europe.Methods:PM2.5 emissions from vegetation fires in Europe in 2005 and 2008 were evaluated based on Moderate Resolution Imaging Spectroradiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 46 publications
1
47
0
Order By: Relevance
“…Geospatial emissions inventories provide input into the Finnish Meteorological Institute’s (FMI) System for Integrated modeLling of Atmospheric coMposition (SILAM) 27 29 . SILAM was run at geospatial resolution of 10 x 10 km and a temporal resolution of 3 h (see Methods section).…”
Section: Resultsmentioning
confidence: 99%
“…Geospatial emissions inventories provide input into the Finnish Meteorological Institute’s (FMI) System for Integrated modeLling of Atmospheric coMposition (SILAM) 27 29 . SILAM was run at geospatial resolution of 10 x 10 km and a temporal resolution of 3 h (see Methods section).…”
Section: Resultsmentioning
confidence: 99%
“…Too little data is available on the specific risks of wildfire smoke to make a conclusive comparison between wildfire smoke mortality and mortality from other air pollution sources. Many studies have found small associations between increased particulate matter due to wildfires and overall mortality (Johnston et al, 2011; Kollanus et al, 2017; Morgan et al, 2010; Sastry, 2002). However, at least one study suggests that the mortality rate observed during wildfire events is consistent with the increase in mortality from elevated PM 2.5 , regardless of source (Hänninen et al, 2009).…”
Section: Health Effects Of Wildfire Smokementioning
confidence: 99%
“…Four of five studies reported small increases in wildfire smoke associated mortality among all ages, however, all confidence intervals included the null [18][19][20][21]. The fifth study reported positive odds ratios (ORs) on lag days 0, 2, 3, and 4, but not on lag day 1 [22]. A study in Finland reported a 0.8% (95% CI: −3.5 -5.3%) increase in all-cause mortality per 10 μg/m 3 increase in same-day PM 2.5 concentration [19], while another study in Australia estimated that wildfire events were associated with a 2.0% (95% CI: −2.0 -5.0%) increase in the odds of same-day non-accidental mortality [21].…”
Section: Introductionmentioning
confidence: 96%